Lubomirski y el Teatro Español del Siglo de Oro - Presa González, Fernando (Eslavística Complutense, 2003)
Stanislaw Herakliusz Lubomirski represents, in the Polish theatre, the most important attempt to create a national comedy modeled on Spanish and Italian theatre. Among his numerous theatrical works, there are two works which, though based on Boccaccio’s novels, show obvious influence of the Spanish Golden Age comedy. They are Old Lopes and Spirydion (Komedyja Lopesa starego ze Spirydonem) and Don Alvares or Bad Company in Love (Don Alvares albo Niesfoma w milosci kompanhja).